Implementasi Konsep Langendriya Mandraswara terhadap Seniman Muda - Sutarno Haryono (PANGGUNG, 2012)
Culture, especially the arts of the palace, is understood to be court arts full of symbols and com- plexity, representing the philosophy of the king with high values and meaning. Langendriya Man- draswara first appeared in the Mangkunegaran, during the reign of Mangkunegara IV (1853-1881), integrating verbal and non-verbal components, with effective, communicative, expressive, and aes- thetic meaning. The spirit of Langendriya Mandraswara is a source of inspiration for young artists.Â Keywords: Langendriya Mandraswara concept, Verbal and non-verbal Language.